Effects of physical foaming of PA66 + 30%GF thick-walled parts - Nowinka Bartosz; Sykutera Dariusz; Konczal Natalia (MATEC Web of Conferences, 2021)
The paper presents the effect of gas dosing parameters on the microporous structure of physically foamed polyamide 66 reinforced with 30 wt% of glass fibers (PA66 + 30% GF). The thick-walled molding was used as the research object. To realize the research aim, simulation software was applied. The variable parameter in a research program was a dose of supercritical fluid, in this case, nitrogen. The tested properties of a cellular structure were: cell size, cell density and local density of a material. All the parameters were considered based on 30 measurement points evenly distributed in the central zone of the sample’s cross-sectional area. The largest size of pores was observed in the core region of molding for every amount of supercritical (SCF) fluid used. It was shown that regardless of the amount of gas, the pore size increases as a function of the distance from the mold cavity surface until it achieves a constant value. However, the most rapid increase was observed in the case of the smallest amount of gas dosed (0.25 wt%) which also resulted in the largest pore size in the core zone of a molding. The lowest value of cell density was noticed for 0.25 wt% of gas used. In the case of 0.5 wt%, 0.75 wt% and 1 wt% of gas dosed, results of cell size, as well as cell density, were comparable. However, dosing 1 wt% of gas resulted in obtaining the finest structure, characterized by the smallest pore size and highest cell density. As a parameter resulting from a cell size and cell density, the local density of material was analyzed. The lowest value of local density in the core area was noticed for 0.25 wt% of SCF dosed.